A hesitant fuzzy linguistic bidirectional projection-regret decision making model. (July 2022) - Ding, Quanyu; Wang, Ying-Ming; Goh, Mark; Rodríguez, Rosa M.; Martínez, Luis
Highlights: The DMs elicit their subjective preferences with CLEs based on HFLTs. Several HFLTS-BPMs are defined. BPMs-RT measures based on HFLTS are proposed. A method for finding the attribute weight is proposed. Abstract: Real-world decision-making problems are usually defined under uncertain contexts due to their complexity. In such situations, the psychological behavior of decision makers is often ignored, and it is assumed that they can provide accurate knowledge despite of being in a context defined as 'uncertain'. Such assumptions are not realistic and may bias final decisions. To overcome such problems, this paper aims to consider the psychological behavior of decision makers and facilitate preference modeling under uncertainty in the decision-making process. It will do so by introducing a novel decision-making model that includes new bidirectional projection-based regret theory (RT) measures under a hesitant fuzzy linguistic term set (HFLTS) environment, thus establishing novel utility and new regret-rejoice functions to handle decision-making situations. Eventually, a supplier selection case study is used to show the performance of the proposed method, and a fair comparison with two existing methods is carried out to illustrate the advantages of our method.